Вплив попередників на урожайність сортів пшениці м’якої озимої в Північному Степу України - Любченко, Єгор Володимирович; Liubchenko, Yehor (ЦНТУ, 2023)
В даній кваліфікаційній магістерській роботі вивчено вплив попередників на урожайність сортів пшениці м’якої озимої в Північному Степу України. Мета досліджень – з’ясувати вплив попередників на урожайність сортів пшениці м’якої озимої в Північному Степу України. Встановлено, що для збільшення рівня урожайності зерна та економічної ефективності при вирощуванні пшениці м’якої озимої в умовах Північного Степу України на чорноземі звичайному середньогумусному сівбу після попередника соя проводити сортом Катруся одеська (умовно-чистий дохід при цьому становив 12635 грн./га, рентабельність 62,8 %), а після соняшника – вищий умовно-чистий дохід 10096 грн./га та рівень рентабельності 50,8 % був у сорту Наснага. In this qualifying master's thesis, the influence of predecessors on the yield of soft winter wheat varieties in the Northern Steppe of Ukraine was studied The purpose of the research is to find out the influence of predecessors on the yield of soft winter wheat varieties in the Northern Steppe of Ukraine. It was established that in order to increase the level of grain yield and economic efficiency in the cultivation of soft winter wheat in the conditions of the northern steppe of Ukraine on the usual medium-humus chernozem, sowing after the predecessor of soybeans should be carried out with the Katrusia Odeska variety (conditionally net income was UAH 12,635/ha, profitability 62.8%), and after sunflower, the Nasnaga variety had the highest conditional net income of UAH 10,096/ha and a profitability level of 50.8%.
The influence of predecessors on the yield of soft winter wheat varieties in the Northern Steppe of Ukraine
Keywords: урожайність; пшениця озима; попередники; productivity; winter wheat; predecessors